Impact of dividend policy on return on assets: evidence from listed non-financial firms in Sri Lanka. - Ravindran, M.; Kengatharan, L. (Sri Lanka Journal of Banking and Finance ISSN 234-9271 Volume: 3 Issue 02 December 2020, 2020)
The dividend policy of a firm is considered as a crucial decision among the management of the organizations. Therefore, the study developed to find out the impact of dividend policy on return on assets of the non financial firms listed in Sri Lanka, using a randomly selected sample of 100 firms listed in the Colombo Stock Exchange for the period from 2013 to 2017. To test the hypothesis, the study incorporated dividend pay-out ratio, dividend per share as independent variables, sales growth, leverage as a control variable, and return on assets as a dependent variable. Initially the unit root test is carried out to test the stationary of the data set. Descriptive statistics, correlation analysis, and pooled OLS were carried out as research techniques and found that dividend per share significantly impacts on return on assets, and the other hand dividend pay-out ratio does not significantly impact on return on assets of the non – financial firms listed in Sri Lanka. The results suggest that the dividend decisions significantly contribute towards the profitability and therefore, considerable attention is required over the dividend decisions of the organizations and this should be revaluated to serve the investor’s potential expectations.
Keywords: Dividend pay-out; Dividend per share; Return on assets